ANALISA RISIKO KECELAKAAN KERJA DENGAN MENGGUNAKAN METODE FMEA (FAILURE MODE AND EFFECT ANALYSIS) - Fari Fatullah (JURNAL TECHLINK, 2020)
The purpose of the study was to analyze the risk of work accidents using the FMEA (Failure Mode and Effect Analysis) method at the Bukit Tua ORF project at PT Raga Perkasa Ekaguna, Madura in 2018. The study used a descriptive method with a qualitative approach. The results showed the ranking of severity scale, failure mode with the highest scale with a value of 10 is the object falling on the lifting by crane activity and on the type of accident the collapsing excavation wall fell upon workers on the activity. The smallest severity scale of failure mode is exposed to UV rays for a long time with a scale of 2. The occurance scale, the highest cause of failure mode is a sling or broken steel rope with a value of 7 in lifting by crane activities. As for the occurance scale, the lowest cause of failure mode is the distance between workers too close to the value of 1 on the activities of road, drainage, foundation. The highest scale of detection, cause of failure mode is to ensure the condition of the equipment before work begins with a value of 7 in lifting by crane activities. The lowest detection scale is the distance between workers too close to the value 1. The highest RPN calculation result is the lifting by crane activity that causes the object to fall, with an RPN value of 490. Improvement of Fishbone diagram results, to humans or workers by providing training on hazards caused by lifting by crane activities, the chief coordinator or supervisor is expected to always supervise the performance of his subordinates. Machines, by conducting routine checks on each of the tools used in crane lifting activities. Regular company checks can schedule regular repairs to these tools. The method, by making SOPs and lifting plans correctly that is by using the right calculations, can be done by coming directly to the work area and doing simulations using cranes that will be used as well as seeing the material to be raised in this activity. So that the data obtained to make SOP and or lifting plan are accurate so that it gets a precise calculation. Environment, by installing barriers or prohibited signs to pass, so that no unauthorized person enters the area during the appointment. Check the condition of the soil so that it remains stable in the lifting area by the crane.